An update on the Apocynaceae in Thailand - Middleton, David J. (Thai Forest Bulletin (Botany), 2014)
Since publication of the Flora of Thailand Apocynaceae account in 1999 there have been developments in our understanding of the relationships within the family, some changes in generic delimitations, new species described and new records found. The current information is synthesised, a new key to genera presented, and keys to the species in altered genera given.